2020
DOI: 10.1161/jaha.119.015610
|View full text |Cite
|
Sign up to set email alerts
|

Age, Sex, and Valve Phenotype Differences in Fibro‐Calcific Remodeling of Calcified Aortic Valve

Abstract: Background In calcific aortic valve disease on tricuspid aortic valves ( TAVs ), men have higher aortic valve calcification and less fibrosis than women. However, little is known in bicuspid aortic valves ( BAV ). We thus aimed to investigate the impact of age, sex, and valve phenotype ( TAVs versus BAVs ) on fibro‐calcific remodeling in calcific aortic valve disease. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 44 publications
1
71
0
Order By: Relevance
“…In a study by Tromsø, Cox proportional hazards regression was used, with age (hazard ratio 1.11, 95% CI: 1.08–1.14) identified as an independent predictor for incident CAVD [ 12 ]. Recently, a cohort study disclosed that aortic valve calcification density was related to age (β estimate±standard error: 6.5±1.8; p=0.0004) in a multivariate analysis [ 13 ]; the potential causes may include activation of the renin–angiotensin system and alteration of the phosphocalcic metabolism in older patients [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Tromsø, Cox proportional hazards regression was used, with age (hazard ratio 1.11, 95% CI: 1.08–1.14) identified as an independent predictor for incident CAVD [ 12 ]. Recently, a cohort study disclosed that aortic valve calcification density was related to age (β estimate±standard error: 6.5±1.8; p=0.0004) in a multivariate analysis [ 13 ]; the potential causes may include activation of the renin–angiotensin system and alteration of the phosphocalcic metabolism in older patients [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the possible differences during the progression of CAVD, several recent studies have been conducted. A recent study demonstrated that, compared to men, women with AS had more pronounced fibrotic remodeling, irrespective of the valve morphology or age of the patient [32]. The same study also showed that, in CAVD, AS hemodynamic severity may not be correlated to the degree of AVC in young women with BAV so that these women may have a hemodynamically severe AS with no or minimal AVC load.…”
Section: Development Of the Clinical Phenotypesmentioning
confidence: 95%
“…Genomic studies, primarily characterized from adult end-stage phenotypes, show complex genetics with dissimilar patterns of inheritance, genetically heterogenous phenotypes, and multiple chromosomal regions that impact the ECM network directly or indirectly 45 , 47 49 . Gender may also play a role—while bicuspid aortic valve is three times as likely to be found in males, females have more collagen deposition and less calcification 50 , 51 . Surgical replacement of valves is an option in adults, but in children, valve replacements do not grow with the patient, leading to heart dysfunction and failure 4 , 52 .…”
Section: Discussionmentioning
confidence: 99%